The Relevance of Islamic Economics and Finance Fundamentals to the Contemporary Economy: Islamic Economist Perceptions - Andri Soemitra (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2021)
There have been some studies related to the fundamental values of Islamic economics and finance. However, not many studies directly examine the relevance of the fundamental values of Islamic economics and finance to the modern contemporary economy. This study intends to examine the perception of Islamic economists on the relevance of the fundamental values of Islamic economics and finance to the contemporary economy. This research was conducted with a qualitative design by conducting a structured survey and in-depth interviews with 61 participants. Data analysis used in this research is collected from surveys and interviews from several sources and analyzed by qualitative descriptive method. The findings show that the Islamic economists perceived that the Islamic economics and finance fundamental values are relevant to contemporary modern economic conditions. The values are also considered better in overcoming economic and financial problems, thus achieving Islamic goals of public prosperity. The results also reveal the need for more vigorous efforts in promoting Islamic economics and finance fundamental values.==========================================================================================================ABSTRAK – Relevansi Fondasi Ekonomi dan Keuangan Islam dengan Ekonomi Kontemporer: Persepsi Ekonom Islam. Kajian-kajian terkait dengan nilai-nilai dasar ekonomi dan keuangan Islam telah banyak dijumpai dalam literatur. Namun, tidak banyak penelitian yang secara langsung mengkaji relevansi nilai-nilai fundamental ekonomi dan keuangan Islam dalam tataran ekonomi kontemporer. Oleh karena itu, penelitian ini bertujuan untuk mengkaji persepsi ekonom Islam terhadap relevansi aspek fundamental ekonomi dan keuangan Islam dalam terhadap ekonomi kontemporer. Penelitian ini dilakukan dengan pendekatan kualitatif dimana data-data didapat dengan cara survei terstruktur dan wawancara mendalam dengan 61 peserta. Analisis data dilakukan dengan metode deskriptif kualitatif. Hasil kajian menunjukkan bahwa para ekonom Islam menganggap bahwa nilai-nilai fundamental ekonomi dan keuangan Islam relevan dengan kondisi ekonomi kontemporer. Nilai-nilai tersebut juga dianggap lebih baik dalam mengatasi masalah ekonomi dan keuangan kontemporer, sehingga mencapai tujuan syariah untuk kesejahteraan umat. Hasil kajian juga mengungkapkan tentang pentingnya upaya yang lebih gencar dalam mempromosikan nilai-nilai fundamental ekonomi dan keuangan Islam.